Expression of the human immunodeficiency virus envelope glycoprotein is restricted to basolateral surfaces of polarized epithelial cells. - Owens, R J (1989)
Polarized epithelial cells exhibit apical (lumenal) and basolateral (serosal) membrane domains that are separated by circumferential tight junctions. In such cells, enveloped viruses that mature by budding at cell surfaces are released at particular membrane domains. We have used a vaccinia virus recombinant to investigate the site of surface expression of the human immunodeficiency virus type 1 envelope glycoprotein in Madin-Darby canine kidney cells. Cells were infected with the vaccinia virus recombinant, and surface expression of the glycoprotein was analyzed by indirect immunofluorescence, 125I-protein A binding, and immunoelectron microscopy. The glycoprotein appeared exclusively at the basolateral surface as early as 2 h postinfection and reached a maximum level at 8 h postinfection. The gp120 glycoprotein was found to be secreted efficiently into culture medium, and this secretion occurred exclusively at the basolateral surface.